Prevalence and associated factors of urinary incontinence among adult women in primary care - Narcicegi, Bilge Alkurt; Yakar, Burkay; Narcicegi, Harun Recep; Onalan, Erhan; Pirincci, Edibe (Cukurova Univ, Fac Medicine, 2021)
Purpose: The current study aimed to prevalence of urinary incontinence (UI) and related factors in adult women admitted to the family medicine outpatient clinic. Materials and Methods: This cross-sectional prospective study was conducted in a family health centre between October 2020 and March 2021. Randomly selected 268 adult women were included in the study. The demographic, obstetric, gynecological characteristics and medical history of the participants were obtained with a questionnaire. Urinary incontinence symptoms was assessed using Turkish Version of the International Incontinence Questionnaire Short Form (ICIQ-SF) Results: The prevalence of UI in study population was 17.5% and according to age grup it was 4.1% at 18-29 years, 10.3% at 30-39 years, 12.0% at 40-49 years, 33.3% at 50-59 years, 46.7% at 60-69 years and 81.8% at >= 70 years old, respectively. Participants with urinary incontinence had higher median age, body mass index (BMI), menopause vintage, and gravida than continent participants. Low education level, drug usage, constipation, menapause (were independently associated with urinary incontinence. Conclusion: UI is still a common health problem among adult women. We recommend physicians to be questioned about UI symptoms, especially in women over 50 years of age. Further studies are needed to evaluate the effect of the treatment of modifiable risk factors on UI incidence among adult women.
Keywords: Urinary Incontinence; female; prevalence; family practice